2009
DOI: 10.1021/jp909428r
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Calculations on the Hydrogenation of Carbon Dioxide on Fe(111) and W(111) Surfaces

Abstract: With quantum-chemical calculations, we investigated the hydrogenation of a CO2 molecule on Fe(111) and W(111) surfaces using the density functional theory (DFT) with the projector-augmented wave (PAW) approach in periodic boundary condition. The structures and geometric parameters of the hydrogenation products, and the potential-energy surfaces, were calculated. It was shown that similar reaction paths for the hydrogenation of CO2 on Fe(111) and W(111) surfaces were found but with disparate energies. The rate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 54 publications
(58 reference statements)
0
51
0
Order By: Relevance
“…Their simulations of CO 2 dissociation on Fe(111) surface showed that the catalytic process is likely to proceed via a three-step mechanism. Li et al [198] with the use of PAW method in conjunction with the rPBE functional studied microkinetic modelling of CO 2 hydrogenation on Fe(111) surface. They found out that the most probable path for the hydrogenation of CO 2 on Fe(111) surface is the formation of a formate-vertical structure.…”
Section: Fe Catalytic Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their simulations of CO 2 dissociation on Fe(111) surface showed that the catalytic process is likely to proceed via a three-step mechanism. Li et al [198] with the use of PAW method in conjunction with the rPBE functional studied microkinetic modelling of CO 2 hydrogenation on Fe(111) surface. They found out that the most probable path for the hydrogenation of CO 2 on Fe(111) surface is the formation of a formate-vertical structure.…”
Section: Fe Catalytic Surfacesmentioning
confidence: 99%
“…Their simulations of CO 2 dissociation on Fe(111) surface showed that the catalytic process is likely to proceed via a three‐step mechanism. Li et al . with the use of PAW method in conjunction with the rPBE functional studied microkinetic modelling of CO 2 hydrogenation on Fe(111) surface.…”
Section: Modelling Catalyst Surfacesmentioning
confidence: 99%
“…It is possible that the reaction proceeds via either formate (HCOO) [Scheme (a)] or carboxylate (COOH) as an intermediate [Scheme (b)]. It has previously been reported that the adsorption of HCOO on iron surfaces is more stable than that of carboxylate . Thus, it may be expected that the first step in the mechanism of formation of heptanal and 2‐octanone is the formation of formate.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that the reactionp roceeds via either formate (HCOO)[ Scheme 1(a)] or carboxylate (COOH) as an intermediate [Scheme 1(b)].I th as previously been reported that the adsorptiono fH COO on iron surfaces is more stable than that of carboxylate. [69,70] Thus, it may be expected that the first step in the mechanism of formation of heptanal and 2-octanone is the formation of formate.H owever,i th as been observed (e.g., Figure2)t hat liquid species formed during the hydrothermal conversion of CO 2 in the present work maintained the C=O double bond. This is consistentw ith the carboxylate mechanism for which the C=Ob ond is preserved through all steps.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…Recent experimental studies showed that quercetin can used as a potential corrosion inhibitors against C38 steel [21] due to the presence of heteroatoms. Fe(111) surface was chosen for this study, as it is more reactive and has a very open surface structure [50,51]. Due to the planar structure of quercetin backbone, a parallel interaction between the metal surface and the molecule was expected to occur which would enable facile adsorption of the molecule.…”
Section: Methodsmentioning
confidence: 99%